A contribuição educativa da biblioteca escolar no contexto da educação infantil: aprendizagem ao longo da vida do educando como cidadão aprendente - Costa, Lidiane Rodrigues dos Santos da (2023)
The importance of cultural spaces such as school libraries in Early Childhood Education is questioned, at the same time that we question how children's interaction with literature (fables, short stories, poetry, etc.) can contribute to their social and educational development of the child at this stage of formal education. This study has the general objective of analyzing the contribution of the school library in the context of early childhood education and for learning throughout the student's life. As for the specific objectives, it proposes: Survey scientific literature on the research themes represented by the analysis categories: “Information Science and Education” and “Information, library and early childhood education”; Knowing the historicity of the school library in Brazil and the importance of librarians working in them, together with their potential for the formation of citizens in childhood; Identify the Public Teaching Institutions of Early Childhood Education in which there are libraries located in the Metropolitan Region of Greater Vitória (RMGV); and To analyze, in the light of the legislation, the pedagogical processes of teaching and learning of school institutions that can contribute to early childhood education. This qualitative research is classified as exploratory in terms of objectives, and in terms of procedures it is constituted as “bibliographic and documental”. For this, theoretical works by Information Science and Education researchers such as Aida Varela and Paulo Freire were consulted, as well as searches were carried out in the following databases: Google Scholar, References of Journal Articles in Information Science (BRAPCI) and the Brazilian Digital Library of Theses and Dissertations (BDTD – IBICT), as well as we consulted books and obtained directive educational documents such as: PNE, BNCC, DCNEI, LDB and IFLA. Although the BNCC's early childhood education document and the DCNEIs do not provide for the existence or use of spaces such as BE in early childhood education institutions, in everyday practice it is extremely possible to develop plans for pedagogical activities involving the use of resources relevant to this space and, mainly, that they contemplate the requirements related to the fields of experiences destined to early childhood education. We were also able to observe the relevance of normative legislation such as the BNCC and the DCNEIs for the teaching and learning process of children enrolled in early childhood education, as well as for the curricular content to be covered in this teaching stage. Access to literary materials, as well as their access to suitable environments to access them, together with the mediation of a professional librarian, is, and always will be, of great value for better training throughout life, as well as in practice. citizenship of children who attend school libraries in kindergarten, but this possibility seems somewhat distant to us.